TINJAUAN PELEPASAN INFORMASI MEDIS PASIEN RAWAT JALAN KEPADA PIHAK KETIGA ASURANSI KESEHATAN SWASTA DI RUMAH SAKIT SETIA MITRA JAKARTA - Meliana; Adeani Putry (MEDICORDHIF Jurnal Rekam Medis, 2022)
The release of medical information is a procedure for releasing, disseminating, and disclosing data or patient medical information for other purposes that do not harm the patient which has been regulated by law, medical information can be provided to insurance, the patient or the patient's family, the hospital that is the place of referral, other doctors treating patients, and for court purposes. The research method used is a type of qualitative descriptive analysis research method. Of the 8 requests that do not meet the requirements, there are 7 requests and there is 1 request that meets the requirements. It is not appropriate because the insurance company does not fully carry the requirements for the release of medical information at Setia Mitra Hospital and still releases medical information to third parties even though the requirements are incomplete or not according to the procedure. The conclusions from the release of medical information to third parties are: Setia Mitra Hospital already has a Standard Operating Procedure (SPO) regarding the release of medical information to third parties which contains the meaning, objectives, policies and procedures. The application of this SOP is not yet fully consistent, the release of medical information to third parties at Setia Mitra Hospital is only carried out for health insurance claim requirements, at Setia Mitra Hospital there is no expedition book or checklits sheet for data collection on the release of medical information to third parties only using file sheets placed on the staff's dsk. Bibliography : 6 pieces (1994-2015) Keywords : Discharge, Medical Information, Outpatient, Third Party